ANALISIS KUALITAS LAYANAN E-COMMERCE TERHADAP KEPUASAN PELANGGAN (STUDI KASUS : RUMAH KERAJINAN KAYU SITUBONDO) - Windiawati, Windiawati; Sari, Maheni Ika (Relawan Jurnal Indonesia, 2022)
The research objective was to determine and analyze the effect of efficiency, fulfillment, system availability, privacy, and partial responsiveness to customer satisfaction. The theories used in this research are marketing management theory, service quality theory, and customer satisfaction theory. The research was conducted on customers of the Wooden Craft House. This type of descriptive quantitative research using purposive sampling method with a sample of 82 respondents. The nature of the research is explanatory. The test tool used is multiple linear regression, with SPSS software version 20.00. The t test results show that efficiency (0.003), fulfillment (0.006), system availability (0.001), privacy (0.000), and responsiveness (0.002) have a significant effect on customer satisfaction partially. The regression test shows that efficiency (0.155), fulfillment (0.195), system availability (0.189), privacy (0.220), and responsiveness (0.210) have a positive effect on customer satisfaction and the coefficient of determination test is 93.7%, customer satisfaction is influenced by efficiency. , fulfillment, system availability, privacy, and responsiveness while the remaining 6.3% is influenced by other variables outside of research.